Roles of Mesenchymal Stem Cell-derived Extracellular Vesicles in Cancer: Development and Target Therapy - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2025)
Extracellular vesicles (EVs) are membrane structures that enclose proteins, lipids, RNAs, metabolites, growth factors, and cytokines. EVs derived from mesenchymal stem cells (MSCs) can either stimulate or inhibit tumor growth in various malignancies through paracrine signaling. Tumor-associated MSCs (TA-MSCs), often described as "wounds that never heal," actively participate in the development, propagation, and metastasis of tumors, impacting the immunological state of the tumor microenvironment. For instance, TA-MSCs can alter immune cell recruitment and cytokine production, leading to a pro-tumorigenic environment. Consequently, both the tumor and its microenvironment undergo functional alterations, the cargo of exosomes is modified, and an abnormal tumor-associated MSC phenotype is acquired. MSC-EVs contain exosome microRNA with both tumor-inhibitory and tumor-supportive effects. For example, MSC-EVs have been shown to deliver tumor-suppressive microRNAs that inhibit cancer cell proliferation and induce apoptosis. This review outlines the criteria for the modification, isolation, and characterization of exosomes, as well as their application in cancer, providing insights for clinical use. By understanding these mechanisms, we can better harness MSC-EVs for therapeutic purposes.Keywords: mesenchymal stem cell, extracellular vesicle, exosome, cancer therapy, drug delivery